2011
DOI: 10.1080/00036840802467073
|View full text |Cite
|
Sign up to set email alerts
|

Long-run purchasing power parity with asymmetric adjustment: further evidence from African countries

Abstract: This study applies threshold cointegration test advanced by Enders and Siklos (2001) to investigate the properties of asymmetric adjustment in long-run Purchasing Power Parity (PPP) in 22 selected African countries during the period of January 1980 to December 2003. Although there is evidence of long-run PPP for most African countries, the adjustment mechanism is asymmetric. These results have particularly important policy implications for African countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…To address this issue, Anoruo, Liew, and Elike (2006) employed Kapetanios, Shin, and Snell (2003) nonlinear ADF unit root test and found support for the PPP in 11 out of 13 African countries, a much higher success rate than studies that used the linear ADF test. A similar outcome was also observed by Chang, Lu, Tang, and Liu (2011) who incorporated asymmetric adjustment and nonlinearity into testing procedure. The success rate was further increased to 60 per cent when Yilanci and Eris (2013) considered nonlinear unit root tests and allowed multiple structural breaks using Fourier expansion.…”
Section: The Ppp Literature In Africasupporting
confidence: 82%
“…To address this issue, Anoruo, Liew, and Elike (2006) employed Kapetanios, Shin, and Snell (2003) nonlinear ADF unit root test and found support for the PPP in 11 out of 13 African countries, a much higher success rate than studies that used the linear ADF test. A similar outcome was also observed by Chang, Lu, Tang, and Liu (2011) who incorporated asymmetric adjustment and nonlinearity into testing procedure. The success rate was further increased to 60 per cent when Yilanci and Eris (2013) considered nonlinear unit root tests and allowed multiple structural breaks using Fourier expansion.…”
Section: The Ppp Literature In Africasupporting
confidence: 82%
“…Caporale and Gil‐Alana (2010) employed fractional integration method and found that there was no support for the presence of the PPP in South Africa. Chang et al . (2011) examined the PPP hypothesis among a sample of 22 African countries from the nonlinear point of view by using monthly data over the period 1980‐2003.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a growing consensus that real exchange rate exhibits nonlinearities, and, consequently, conventional unit-root tests, such as the Augmented Dickey Fuller (ADF) test, have low power in detecting mean reversion of exchange rate. To be sure, a number of studies have provided solid empirical evidence for the nonlinear and/or asymmetric adjustment of the exchange rate in developed countries (Baum et al, 2001;Taylor et al, 2001), in the G7 countries (Kilian and Taylor, 2003), in the Middle East (Sarno, 2000), in Asian economies (Enders and Chumrusphonlert, 2004), in African countries (Chang et al, 2009a, Chang et al, 2009b, as well as in ten Latin American Integration Association countries (Chang et al, 2009a, Chang et al, 2009b. It is important to note, nevertheless, that under no circumstance does the finding of nonlinear adjustment necessarily signify the existence of nonlinear mean reversion or stationarity.…”
Section: Introductionmentioning
confidence: 99%